Cloze Tests as Retrieval Practice Activities: Evaluating Their Integration with Audience Response Systems in K-12 Schools - Lopez-Villarroel, M; Ponce-Arias, H (Springer Science and Business Media B.V., 2025)
This study examines the impact of incorporating cloze tests during pauses in classroom instruction as retrieval practice activities, using Audience Response Systems (ARS) for delivery. While ARSs traditionally rely on multiple-choice questions, cloze tests offer a potentially efficient alternative that aligns with retrieval practice principles. Two experiments were conducted to evaluate the efficacy of inserting computer-administered cloze tests during pauses in classroom slideshow lessons using an application called i-cloze. Experiment 1 involved 82 fifth-grade students learning history, and Experiment 2 involved 95 tenth-grade students in English as a Foreign Language (EFL) lessons. Results from Experiment 1 showed no significant benefits of the i-cloze method, likely due to cognitive overload imposed by the content design, the i-cloze tasks, and limited familiarity with the technology. Experiment 2 demonstrated significant improvements in memory and partial improvements in comprehension for students in the i-cloze condition. These findings suggest that cloze-based retrieval practice, when appropriately aligned with lesson content and student readiness, holds promise as an innovative ARS format. EFL contexts may be especially well suited for this approach. Future research should explore how task complexity, content type, and technological familiarity influence the effectiveness of the i-cloze method in diverse educational settings. © The Author(s), under exclusive licence to Springer Nature B.V. 2025.